A review on atomic layer deposited buffer layers for Cu(In, Ga)Se2 (CIGS) thin film solar cells: Past, present, and future. (October 2020) - Sinha, Soumyadeep; Nandi, Dip K.; Pawar, Pravin S.; Kim, Soo-Hyun; Heo, Jaeyeong
Graphical abstract: Abstract: CIGS-based thin film solar cell (TFSC) technology is emerging as a promising contributor to the solar photovoltaic industry next to the presently leading Si-based technology. Although the theoretical limit of power conversion efficiency ( PCE ) is as high as 33.5%, the highest experimental PCE so far just exceeded 20% in the past several years. Therefore, significant efforts are still continuing for further performance enhancement of these cells. Considering that the buffer layer has been identified as one of the key factors, the efforts to replace state-of-the-art but toxic CdS buffer layer have yielded promising results. Several studies showed that the alternative buffer layers grown with environmentally benign materials could even produce a better performance than the CdS-based TFSCs. In this regard, atomic layer deposition (ALD) has been proved as one of the best techniques for depositing the alternative buffer layers. Several Zn-based ternary and few other binary ( e.g. In2 S3 ) compounds have been investigated to realize an optimum ALD-grown buffer layer. In the recent year, a record PCE of 23.35% was achieved using ALD-grown ZnMgO buffer layer along with chemical bath deposited Zn(O, S, OH) for CIGSSe TFSC. However, in general the ALD-grown buffer layers only could provide PCE s well below 20%. The article presents a comprehensive survey on rapid increase in PCE for several ALD-grown buffer layers during the early period followed by a trend of saturation. Finally, the article discusses the current challenges and future scopes/possibilities for the ALD-grown buffer layers as potential alternatives of CdS toward practical applications of CIGS TFSC.